Teacher self-efficacy in relation to cultural and linguistic diversity in K–12 settings: a systematic review - Peterson, Jacqueline Michelle; Jensen, Maria Therese (Frontiers in Education, 2025)
Global migration continues to significantly increase the cultural and linguistic diversity of societies and schools. Consequently, teachers must differentiate instruction and demonstrate cultural awareness to achieve educational equity in their classrooms. However, the extent to which teachers feel efficacious in doing so remains unclear. Previous reviews indicate that teacher self-efficacy impacts wellbeing and instruction. However, there do not appear any reviews that have extended our understanding of the situatedness of self-efficacy within culturally and linguistically diverse (CLD) classrooms. Using the job demands-resources theory as our guiding theoretical framework, we conducted a systematic review (2014–2023) to analyze factors supporting teacher self-efficacy in CLD classrooms and its implications for work outcomes and job performance. There were 19 studies included in the review. Results showed CLD composition positively relates to teacher self-efficacy in teaching in multicultural classrooms. The review revealed multiple job resources, categorized as either universal or unique to CLD settings, that foster teacher self-efficacy within CLD classrooms. Depth of experience with CLD learners was found to be an important characteristic of teachers with high self-efficacy. Teacher self-efficacy related negatively to burnout and positively to job performance. Extending the JD-R model, teacher self-efficacy also emerged as an important predictor of various cognitive outcomes, including teachers attitudes toward diversity and expectations for students. This review shows teacher self-efficacy in CLD classrooms is an emerging and important area of research. The findings presented offer practical implications for improving teacher self-efficacy in CLD classrooms and highlight areas for future research.